IMPLEMENTASI KONSEP PEMBELAJARAN "ACTIVE LEARNING" SEBAGAI UP AYA UNTUK MENINGKATKAN KEAKTIFAN MAHASISWA DALAM PERKULIAHAN - Ali Muhtadi (MAJALAH ILMIAH PEMBELAJARAN, 2009)
The teaching and learning activities in higher education nowadays have beendominated and focused on the application of exposition or expository learningstrategy. In the exposition learning strategy, lesson materials are presented tothe participants who have the ability to control their own materials. As aconsequence, students are become quite passive since there is no initiative toparticipate in the lecturing and also because of the less conducive conditionwhere students have to develop knowledge by themselves. Students areencouraged to ask questions, raise opinions, or discuss relevant issues. Inorder to improve the students' learning activities in the classroom to becomemore dynamic, we can apply one alternative study using "active learning"approach. The implementation of this learning model can be developed into 8procedures or phases that are: (1) orientation (2) group forming (3) teamworkassignment (4) exploration (5) presentation (6) checking students'understanding and the student 's mastery of learning materials (7) reflectionand feedback, and (8) formative evaluation.